Attitudes toward pharmacological cognitive enhancement—a review - Schelle, Kimberly J.; Faulmüller, Nadira; Caviola, Lucius; Hewstone, Miles (Frontiers in Systems Neuroscience, 2014)
A primary means for the augmentation of cognitive brain functions is ‘pharmacological cognitive enhancement’ (PCE). The term usually refers to the off-label use of medical substances to improve mental performance in healthy individuals. With the final aim to advance the normative debate taking place on that topic, several empirical studies have been conducted to assess the attitudes towards PCE of groups outside the normative academic debate. In this review, we provide an overview of the 40 empirical studies published so far, reporting both their methodology and results. Overall, we find that several concerns about the use of PCE are prevalent in the public. These concerns largely match those discussed in the normative academic debate. We present our findings structured amongst the three most common concerns: medical safety, coercion and fairness. Fairness is divided into three subthemes: equality of opportunity, honesty and authenticity. Attitudes regarding some concerns are more coherent across studies (e.g. coercion), whereas for others we find mixed results (e.g. authenticity). Moreover, we find differences in how specific groups—such as users, nonusers, students, parents, and health care providers—perceive PCE: a coherent finding is that nonusers display more concerns regarding medical safety and fairness than users. We discuss potential psychological explanations for these differences.